De la capture à l’asservissement : Comment la machine Meta remodèle les pratiques des journalistes francophones - Samuel LAMOUREUX; Jean-Hugues ROY (Tic & Société)
This paper analyses the relationship between Meta Platforms’ Facebook app and francophone journalists using Durand's (2020) techno-feudal hypothesis, which asserts that large digital platforms establish predatory relationships with news media. A computational analysis of posts on Facebook pages administered in Belgium, Canada, France, and Switzerland allows us to support Meta's infrastructural capture of news media. It is followed by a qualitative analysis that further confirms that Meta reshapes journalistic practices and creates new dynamics of value extraction.